Usulan Perbaikan untuk Meminimasi Reject pada Unit Produksi Keripik Sanjai Rina Kota Payakumbuh - Dina Rahmayanti; M. Ihsan Ashshiddiqi; Hilma Raimona Zadry; Yumi Meuthia; Lusi Susanti (Universitas Putra Indonesia YPTK Padang, 2023)
Sanjai Rina is one of the small and medium industries (SMEs) that produces and sells sanjai chips. This study aims to identify aspects that cause rejected production in Sanjai Rina. This study uses the Statistical Process Control (SPC) method with the Failure Mode and Effect Analysis (FMEA) approach. The stages of the research started with problem identification, brainstorming, FMEA calculations, and recommendations for improvement. Identifying problems using the required to-quality method and IPO diagrams followed by brainstorming to identify the existing problems using fishbone diagrams in more detail. FMEA calculations design a questionnaire for RPN FMEA calculations by considering severity, occurrence, and detection weighting. The resulting rejected products are broken sanjai, burnt sanjai, and non-crispy sanjai chips. The research results found that the highest cause for each cause of rejection was the same, namely the potential due to low worker skill failure with an RPN FMEA value of 409.6. Several solutions can be proposed from this research, while the priority solutions are making work SOPs and making work instructions for the frying section.